Children's and parents' perspectives on open-label use of placebos in the treatment of ADHD. - Sandler A; Glesne C; Geller G (Child: Care, Health & Development, 2008)
Background The purpose of this study was to examine the efficacy and acceptability of an open-label conditioned placebo dose reduction (CPDR) treatment in 70 children with attention deficit hyperactivity disorder (ADHD). This paper focuses on the qualitative data from the study. Methods Following a double-blind, crossover dose finding procedure to determine each subject's optimal dose of stimulant medication, subjects were randomized to the CPDR treatment or one of two control groups. Outcome measures included parent and teacher ratings of ADHD behaviours and stimulant side effects. Qualitative assessments were based on open-ended interviews of children and parents. Positive responders to CPDR and controls were followed for 3 months to assess persistence of treatment benefits. Results Children randomized to CPDR showed an excellent treatment response, well maintained over time. Parents and children were generally accepting of the treatment. Most parents reported treatment benefits and 80% of the children found the placebo to be useful. Full disclosure of the placebo to parents and children did not appear to negate the placebo's effectiveness. Participation effects and changes in caregiver behaviour may have contributed to positive treatment outcomes. Conclusions Open-label use of placebos as part of CPDR treatment may represent an innovative, ethical way of harnessing the power of placebos in clinical therapeutics.